Analysis of new species retrieved from MIPAS - Cai, S; Dudhia, A (Editrice Compositori s.r.l., 2013)
The Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) instrument which operated on the Envisat satellite from 2002-2012 is a Fourier transform spectrometer for the measurement of high-resolution gaseous emission spectra at the Earth's limb. It operates in the near- to mid-infrared, where many of the main atmospheric trace gases have important emission features. The initial operational products were profiles of Temperature, H2O, O3, CH4, N2O, HNO3, and NO2, and this list was recently extended to include N2O5, ClONO2, CFC-11 and CFC-12. Here we present preliminary results of retrievals of the third set of species under consideration for inclusion in the operational processor: HCN, CF4, HCFC-22, COF2 and CCl4.